2011
DOI: 10.1213/ane.0b013e31821b2227
|View full text |Cite
|
Sign up to set email alerts
|

Forced Needle Advancement During Needle-Nerve Contact in a Porcine Model

Abstract: The severity of structural nerve injury after needle-nerve contact was directly related to force exposure via needle advancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 7 publications
0
34
0
1
Order By: Relevance
“…[1][2][3] Recently, high opening injection pressure (OIP) was reported to detect contact of the needle-tip with the nerve roots during brachial plexus blockade. 4,5 Opening injection pressure monitoring prevented the injection of local anesthetic against the epineurium of the interscalene brachial plexus in 97% of cases.…”
mentioning
confidence: 99%
“…[1][2][3] Recently, high opening injection pressure (OIP) was reported to detect contact of the needle-tip with the nerve roots during brachial plexus blockade. 4,5 Opening injection pressure monitoring prevented the injection of local anesthetic against the epineurium of the interscalene brachial plexus in 97% of cases.…”
mentioning
confidence: 99%
“…Apart from intraneural injections of local anaesthetics, we observed that the puncturing of nerves with larger needles (18G), as used for catheter techniques, could eventually result in fascicular damage and intraneural bleeding 25 . Additionally, we found even myelin injury due to needle advancement during needle nerve contact 26 . In conclusion, paraesthesia seems to specifically indicate either a needle nerve contact or intraneural needle tip position ---where both may lead to nerve injuries.…”
mentioning
confidence: 71%
“…The mechanisms accounting for nerve damage include fascicle trauma, ischaemia and local anaesthetic toxicity 9 . More recently needle-epineurium contact was associated with intraneural haematoma, inflammation and myelin damage in over half of cases in animal studies [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%